Mucormycosis: A Different Perspective after COVID-19 Pandemic - Shailja Prajapati, Digvijay Singh Rawat, Yogesh Aseri, Prankul Khandelwal, P C Verma (RUHS Journal of Health Sciences)
Introduction: Mucormycosis is a fatal but uncommon fungal infection affecting multiple sites like the orbit, the sinuses, lung, brain. After the second wave of COVID-19 pandemic, sudden surge of mucormycosis cases were noted in India. The present article is intended to highlight the difference in mucor in pre-COVID-19 and post-COVID-19 era, factors responsible in reducing the fulminancy and highlighting the measures taken to reduce mortality and morbidity and long-term complications. Methodology: The present prospective observational study was carried out in the Department of Otorhinolaryngology between April 2021 to January 2023. Total 66 confirmed mucormycosis cases were included which were evaluated, operated and were followed-up for prognosis, recurrence and long-term complications. Results: Majority of the patients belonged to the age group of 41-60 years with male preponderance. 45.45% patients were positive for COVID-19 on RT-PCR and 54.5% were negative. Complications that were observed were hypoesthesia of cheek (6.1%), vision loss (6.1%), gum inflammation (4.5%), facial palsy (4.5%), recurrence over palate (4.5%), dacryocystitis, seizures, maggots at surgical site were seen in 1.5% patients only and around 6.1% patients had persisting vision loss in the follow up. Total deaths accounted for 13.6% of patients. Conclusion: Post-COVID-19 mucor is different in term of age of presentation, fulminancy, prognosis, outcome and terms of management however it is similar to pre-COVID-19 mucor in terms of male sex predominance, associated comorbidity, presenting symptoms and commonest clinical form which is ROCM. It has predominance in older age groups compared to mucor in pre-COVID-19 era and has better prognosis and is less fulminant.